Planeación de la gestión del talento humano y diseño organizacional de la empresa productora y comercializadora de productos alimenticios Arpri, en la ciudad de Loja - Lopez Simbaña, Lizeth Jimena (2017)
The thesis work is based on Human Talent Management and Organizational Design in the production and marketing company "ARPRI" products in the city of Loja, which will help it optimize resources and thus achieve institutional objectives. For its development and execution, it was necessary to have the help of a theoretical framework in which all the theoretical foundations of each one of the aspects treated in the investigation are contained, it also required the help of a methodology that allowed to maintain a sequence and order in Each aspect treated to make the different diagnoses, which once made possible the analysis and interpretation of the results. After applying information collection techniques such as the interview conducted to the Manager and the surveys applied to all workers of the company, it was found that it lacks organizational design since it has no established organizational charts: structural, functional and positional ), Manuals of both functions and welcome. It was also found that there are shortcomings in the management of human talent, due to the fact that there is no process of admission of personnel (recruitment, selection, recruitment, induction, qualification training of positions and evaluation of work performance); For the valuation of positions do not use mathematical methods to establish a fair remuneration to the workers only they are based on the Basic Unified Salary, and the evaluation of performance they realize it only verbally; The Manager evaluates each worker. 5 Based on all the analyzes carried out, the proposal for the planning of human talent management and organizational design is elaborated with the purpose of leading the company for improvement, which contains strategic objectives, operational objectives, goals , Actions, responsible and budget of the proposed objectives. Organizational charts: structural, functional and positional; Which will help the company to have a good organizational structure; Here they indicate the positions, the functions that must fulfill, the names of each worker with his respective salary. Manuals: functions and welcome, in order that the members of the company have a clear, concise and updated description of the different activities that must be performed. An adequate process of admission and employment of personnel that shows the correct way to carry out the recruitment, selection, contracting, induction, training; With the intention that the company has the competent workers and thus carry out the activities efficiently. Valuation of positions using the point method, in order to have a good organization and remuneration of the staff according to the requirements of the position and the functions of the same. And an evaluation of performance to the personnel that work in the company, using the method of graphical scale by points; To know if the worker is in the proper position, to know its development and to help improve its performance. All this focused on the company has a good organizational design that can differentiate it from other industries; And a human talent management with which they can have the appropriate personnel that occupy the existing positions, carrying out the activities of efficient and effective way.